Entrepreneur behavior of young educated farmers in the covid -19 pandemic - Nurlaela Siti (EDP Sciences, 2021)
The Covid 19 pandemic has an impact on young farmer entrepreneurs. Business income has dropped drastically, and the distribution process is experiencing difficulties. Entrepreneurial behaviour is needed so that young farmers can cope with the impact of Covid 19. This research seeks to analyze the entrepreneurial behaviour of young farmers during the Covid 19 period. The sample is all educated young farmers who participated in the PWMP program (Agricultural Young Entrepreneur Development)—using a google form from 90 participants who were willing to fill out 71 young farmers. The research variables were: the ability to survive in entrepreneurship (X1), the use of new media for entrepreneurship (X2), and business success during the Covid period (X3). Percentage, mean score, and regression analysis at p ≤ 0.05 were employed to analyze the data. There was a significant effect (p ≤ 0.05) between X1 and X2 on X3 of 28.1%. The ability to survive in entrepreneurship (X1) has a significant effect, while new media for entrepreneurship (X2) is insignificant. The government is expected to protect young farmers' businesses by providing additional capital, marketing and business assistance in collaboration with successful entrepreneurs.